A Survey-Based Investigation of Human Factors Associated With Transport Related Injuries in Horses - Padalino, Barbara; Rogers, Chris W.; Guiver, Danielle; Thompson, Kirrilly R.; Riley, Christopher B. (Frontiers in Veterinary Science, 2018)
Injuries resulting from road transport are common in horses and are a potential welfare concern as well as a source of economic loss. An online cross sectional survey was used to determine the prevalence of road transport related injuries to horses in New Zealand and the association of human factors including demographics, industry background, training and the horse handling experience of the respondents with transport related injury. The survey generated 1133 valid responses that were analysed using descriptive statistics, univariate and multivariate logistic regression analysis. At least one injured horse was reported by 201/1133 (17.7%) respondents as occurring during the two previous years. Only 191 respondents chose to provide further information on when the injury occurred and most injuries (133/191; 69.6%) occurred in transit. The respondent perceived possible reason for injury was reported by 190, and was most frequently thought to be either horse-associated (87/190; 45.8%) or associated with a driver mistake (18/190; 9.5%). Variables that remained as significantly associated with injury in a multivariate model focusing on human factors were experience in horse handling, the industry sector, and the amateur or professional involvement with the horse industry. The odds of injury associated with professionals may reflect greater exposure due to more frequent transport and larger numbers of horses in their care than amateurs. Findings confirm that human factors are associated with the risk of an injury during transport. Although further studies are required to determine if any of these relationships are causative, education on transport best practices with consideration of these factors may mitigate their influence.